KNOWLEDGE AND PRACTICES OF RIVERINE MOTHERS ABOUT VACCINATION - Silva, Ricardo Luiz Saldanha da; Santos, Evelyn Rafaela de Almeida dos; Silva, Elis Maria Rodrigues da; Rodrigues, Ivaneide Leal Ataíde; Andrade, Erlon Gabriel Rego de; Nogueira, Laura Maria Vidal (Cogitare Enfermagem, 2023)
Objective: to analyze the knowledge of riverine mothers about vaccination and its influence on the practice of taking their children for vaccination. Method: qualitative/descriptive study, conducted at the Combú Family Health Unit, Belém-Pará, Brazil, with 30 riverine mothers who had children of vaccination age. Data were produced by individual interviews, whose corpus was analyzed with the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires 0.7, alpha 2, using Descending Hierarchical Classification. Results: the software generated six classes, composing two categories: “Knowledge and practices of riverine mothers about vaccination” and “Importance of health education and the role of health professionals in sharing information about vaccination”. Conclusion: discussing the knowledge of riverside mothers about vaccination and its influence on decision-making allowed a critical reflection on the practices in the daily life of this population, providing health professionals with the opportunity to rethink strategies, especially in educational actions.